Impact of erythromycin on a non-target organism: Cellular effects on the freshwater microalga Pseudokirchneriella subcapitata - Machado, Manuela Dias (2019)
The increasing and indiscriminate use of antibiotics is the origin of their introduction in aquatic systems through domestic and livestock effluents. The occurrence of erythromycin (ERY), a macrolide antibiotic, in water bodies raises serious concerns about its potential toxic effect in aquatic biota (non-target organisms), particularly in microalgae, the first organisms in contact with aquatic contaminants. This study aimed to evaluate the possible toxic effects of ERY on relevant cell targets of the freshwater microalga Pseudokirchneriella subcapitata. Algal cells incubated with significant environmental ERY concentrations presented disturbance of the photosynthetic apparatus (increased algal autofluorescence and reduction of chlorophyll a content) and mitochondrial function (hyperpolarization of mitochondrial membrane). These perturbations can apparently be attributed to the similarity of the translational machinery of these organelles (chloroplasts and mitochondria) with the prokaryotic cells. P. subcapitata cells treated with ERY showed a modification of metabolic activity (increased esterase activity) and redox state (alteration of intracellular levels of reactive oxygen species and reduced glutathione content) and an increased biovolume. ERY induced an algistatic effect: reduction of growth rate without loss of cell viability (plasma membrane integrity). The present study shows that chronic exposure (72 h), at low (μg L-1) ERY concentrations (within the range of concentrations detected in surface and ground waters), induce disturbances in the physiological state of the alga P. subcapitata. Additionally, this work alerts to the possible negative impact of the uncontrolled use of ERY on the aquatic systems.